Infectious encephalitis diagnosis and treatment in immunosupressed patients: a case report and review of literature - Jokubaitis , M.; Valaikienė , J. (Neurologijos seminarai, 2019)
Infectious encephalitis in immunosuppressed patients is a common and urgent condition that requires rapid diagnosis and early treatment. The disease can lead to severe neurological deficit and eventually result in the death of the patient. Usually infectious encephalitis presents with fever, headache, focal neurological deficits, and altered state of consciousness. Immunosuppressed patients pose a great differential diagnostic challenge since clinical symptoms, laboratory findings, and imaging tests are often attenuated and may imitate stroke or other non-infectious diseases. Therefore, infectious meningoencephalitis should be suspected in all immunosuppressed patients with acute focal neurological symptoms, even in the absence of fever and meningeal signs. Accordingly, physician should thoroughly evaluate patient’s history, perform detailed physical examination, and carefully interpret test results. Early diagnosis and initiation of appropriate treatment of bacterial meningoencephalitis correlates with better prognosis for the patient. This article describes an atypical clinical case of a bacterial meningoencephalitis with stroke-like symptoms in a patient with multiple myeloma. In addition, the article reviews clinical presentation, diagnostic and treatment recommendations of infectious encephalitis in immunosuppressed patients.